Genome characterisation and pathogenicity study of low pathogenic avian influenza virus subtype H9N2 isolated in Malaysia - Gunasekara, Erandi Maheshika (2022)
Asian region and posed a significant threat to the poultry industry. Besides, the virus is potentially zoonotic, where it can directly infect mammals and donate its gene segments to create deadly novel subtypes of pandemic concern. Therefore, identifying the genetic evolution, pathogenesis, and host adaptation of the H9N2 virus is of paramount importance. In late 2017, Malaysia reported repeated incidences of H9N2 in commercial birds, including in the breeder and layer flocks. However, the full genome and pathogenicity of the H9N2 viruses have not been studied. Two H9N2 viruses, A/chicken/Malaysia/Negeri Sembilan/UPM994/2018 and A/chicken/ Malaysia/Johore/UPM2033/2019 were isolated from breeder and layer flocks in Peninsular Malaysia, respectively, were molecularly characterized and pathogenic nature in SPF chicken was identified in this study. Phylogenetic analysis revealed that both viruses were multiple genotypes reassortant strains with genes originated from Y280-like (HA gene), F/98-like (NS, NP, PA), G1- like (M and PB2) and Korean-like (PB1), indicating the viruses belong to a novel genotype of a divergent from G57 lineage of Chinese origin. The seven genes namely NS, M, HA, NA, NP, PA and PB2 are closely related to viruses isolated from Indonesia, Taiwan, Japan, and Cambodia. However, the PB1 genes of both viruses are different from other H9N2 viruses detected in the region. They have a 97% similarity with the Korean H9N2 strain A/chicken/Korea/1310/2001. In addition, the virus strain has been developed and used as an inactivated vaccine in Korea and other countries. Deduced amino acids mutations were analysed and compared with previously reported mutation markers that were confirmed by reverse genetic and cell culture experiments. Both Malaysian H9N2 isolates in this study contained the hemagglutinin (HA) Q226L substitution, which favors mammalian receptor type binding. The molecular and deduced amino acid analysis revealed that both viruses possess a dibasic cleavage site at the position 333-PSRSSR-GLF-341 of their respective HA gene cleavage sites. Furthermore, the polymerase complex genes have mammalian adaptation mutation (550L in PA gene) and enhanced pathogenicity markers (A588V in PB2 gene). Both H9N2 viruses were susceptible to the neuraminidase inhibitor antivirals; however, their M2 genes have an S31N substitution which associated with amantadine resistance. Pathogenicity study of one of the isolates, UPM994/2018 was performed in one-weekold specific-pathogen-free (SPF) chickens following inoculation of the virus at 107 EID50 via the oro-nasal route. Clinical signs such as ruffled feathers, mild tracheal rales, gasping, facial edema, sero-nasal discharge and diarrhoea were observed from 6 to 10 days post-inoculation (pi). However, no mortality was recorded. Based on real-time PCR results, the viruses can be detected in the lungs, tracheas, and kidneys of the inoculated chickens on the second day and increased until day 10, then declined at day 16 pi. However, swab samples collected from the oropharyngeal and cloacal remain positive from day 2 to day 14 pi, with the highest viral load detected at day 10 pi. In conclusion, the characterised Malaysian H9N2 virus is a Y280-like virus resembling H9N2 isolated from Indonesia, Taiwan, Japan and Cambodia. However, the virus is a novel genotype of a divergent from G57 lineage of Chinese origin with PB1 gene originated from Korean lineages H9N2 virus. Although the virus is an LPAI, it is pathogenic in SPF chickens causing respiratory, gastrointestinal and renal-associated illnesses.